Self-Empathy in TikTok Comments: A Thematic Analysis of Responses to “Mirrorball” - Nova Karina; Zurriyati; Ainol Mardhiah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examines how listeners express self-empathy in TikTok comments responding to Taylor Swift’s song Mirrorball. While previous research has explored emotional responses to music on digital platforms, limited attention has been given to how individuals direct empathy toward themselves through brief online expressions. Drawing on Neff’s self-compassion framework, this study focuses on three aspects of self-empathy: self-reflection, emotional awareness, and self-validation. Using a qualitative descriptive approach, twelve TikTok comments were purposively selected and analyzed through thematic analysis. The findings reveal that each aspect of self-empathy is equally represented in the data, with four comments categorized under self-reflection, four under emotional awareness, and four under self-validation. These findings show that listeners use the song as a reflective space to recognize themselves, become aware of their emotional states, and validate their feelings through everyday language. These findings suggest that TikTok functions not only as a platform for music consumption but also as a space where individuals articulate and process self-related emotions through brief digital expressions.